2022
DOI: 10.3389/fmolb.2022.839249
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights Into Binding and Activation of the Human KCNQ2 Channel by Retigabine

Abstract: Voltage-gated potassium channels of the Kv7.x family are involved in a plethora of biological processes across many tissues in animals, and their misfunctioning could lead to several pathologies ranging from diseases caused by neuronal hyperexcitability, such as epilepsy, or traumatic injuries and painful diabetic neuropathy to autoimmune disorders. Among the members of this family, the Kv7.2 channel can form hetero-tetramers together with Kv7.3, forming the so-called M-channels, which are primary regulators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…performed a computational-based characterization of this channel in the two not yet observed functional resting-closed (RC) and actived-open state (AO). [43] VSD activation was thought to take place stepwise due to the membrane, proceeding from an initial resting VSD configuration in which the pore is closed (resting/closed, RC) to an activated VSD with an open pore (activated/open, AO), [44] passing through a conformational change of the VSD into an activated state with the pore still closed (activated/closed, AC) as confirmed by the Cryo-EM solved structure of Kv7.2 (PDB ID: 7CR0). [11] In their work, Garofalo et al reported the development and structural validation of new homology models of the human Kv7.2 channel in the RC, AC and AO states.…”
Section: In Silico Approaches For Retigabine Binding Site Modelingmentioning
confidence: 99%
“…performed a computational-based characterization of this channel in the two not yet observed functional resting-closed (RC) and actived-open state (AO). [43] VSD activation was thought to take place stepwise due to the membrane, proceeding from an initial resting VSD configuration in which the pore is closed (resting/closed, RC) to an activated VSD with an open pore (activated/open, AO), [44] passing through a conformational change of the VSD into an activated state with the pore still closed (activated/closed, AC) as confirmed by the Cryo-EM solved structure of Kv7.2 (PDB ID: 7CR0). [11] In their work, Garofalo et al reported the development and structural validation of new homology models of the human Kv7.2 channel in the RC, AC and AO states.…”
Section: In Silico Approaches For Retigabine Binding Site Modelingmentioning
confidence: 99%